PENGARUH LITERASI LINGKUNGAN, PEMBELAJARAN PENDIDIKAN LINGKUNGAN, DAN GAYA HIDUP RAMAH LINGKUNGAN TERHADAP PEMAHAMAN EKONOMI HIJAU PADA SISWA SMP ADIWIYATA DI KABUPATEN PEKALONGAN - Nawa Aprilia, Isna; Nuryana, Ita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In the era of modern educational development, understanding the green economy has become an essential competency that students need to support sustainable development. This study aims to analyze the influence of environmental literacy, environmental education learning, and environmentally friendly lifestyle on students’ understanding of the green economy. The research problem is based on the relatively low level of students’ understanding of green economy concepts, despite the implementation of environment-based programs in schools. This study employed a quantitative approach with an explanatory survey design. The population consisted of 787 students from SMP Negeri 1 Wonopringgo, Pekalongan Regency, with a sample of 265 respondents determined using the Slovin formula. Data were collected through Likert-scale questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that environmental literacy (t = 7.669; p = 0.000), environmental education learning (t = 3.339; p = 0.001), and environmentally friendly lifestyle (t = 5.616; p = 0.000) have a significant direct effect on students’ understanding of the green economy. Furthermore, these variables simultaneously explain 65.4% of the variance in green economy understanding. These findings suggest that strengthening environmental literacy, supported by effective learning processes and the consistent application of environmentally friendly lifestyles, contributes to improving students’ understanding of the green economy.